A afinação do mundo virtual: identidade sonora em jogos digitais - Meneguette, Lucas Correia (2016)
Digital games are one of the main languages of digital culture. As audiovisual, hypermedia and interdisciplinary product, games involve the integration of several professionals in different areas. One of these areas is audio design, which brings together music productions, sound effects and voices in the creation of a sound environment for the game, in close relationship with the fictional universe, with visuality and game design. Although the audio field of study for games already meets a number of academic papers in the last decade, it is a territory still not tamed, especially with regard to the integration of audio within the creation of an aesthetic and functional identity to the game. In this sense, this thesis aims at proposing a conceptual framework that allows us to understand the formation of sonic identity in games, particularly the integration of sound with a “elemental tetrad” made up of aesthetics, mechanics, story and technology. Therefore, it was carried out an extensive bibliography research in various interdisciplinary fields, such as audio for games, sound for cinema, the theory of fictional worlds and the acoustic ecology. Thus, it was possible to reclaim existing concepts and suggest a number of new concepts which helped the aesthetic and functional analysis of individual cases of game sound, such as sound palette, sound profile, sound signature, cosmopoiesis and ludofunctional characterization